Marxist Political Economy: Debates in Cuadernos del Sur (1985-1989) (2024)
The paper analyzes the economic debates in the journal Cuadernos del Sur (CS) in its first period (1985-1989). This, which was characterized by an intellectual perspective of Marxist roots in political economy, constitutes a historical piece of vacancy to capture the controversies in economics of the time. The approach is based on the methodology of analysis of publications from an economic perspective paying attention to the concepts, analysis tools and general vision of their promoters. We argue that the publication maintained an interpretive line with historical roots that identified the contemporary economic crisis of the 1980s as part of a new phase of capitalist restructuring similar to that which developed during the period of the agro-export model (1880-1930). Despite the plurality of intellectual voices that passed through its pages, this analytical framework allowed economic analysis to be framed in a homogeneous way to understand Argentina´s role in the international process.